-1
$\begingroup$

I can't get this to work out right and can't find anything that gives me a rule for how to distribute the $0.5$ here. Any help would be much appreciated.

\begin{align*} 0.5 &=\frac{\exp(-3.6 + 1.8x)}{1 + \exp(-3.6 + 1.8x)}\\ &\\ 0.5(1 + \exp(-3.6 + 1.8x)) &= \exp(-3.6 + 1.8x) \end{align*}

$\endgroup$

4 Answers 4

5
$\begingroup$

OK, so how about seeing that if we write $u=-3.6 + 1.8x$ then we have

\begin{equation} \frac{1}{2}\left(1+e^{u}\right) = e^{u} \end{equation} Now, let's mutiply out the brackets \begin{equation} \frac{1}{2} + \frac{1}{2}e^{u} = e^{u} \end{equation}

so (upon subtracting $\frac{1}{2}e^{u}$ from both sides); \begin{equation} \frac{1}{2} = \frac{1}{2}e^{u} \end{equation} or \begin{equation} 1 = e^{u} \end{equation} Do you think you can solve it now? Then substitute back in for $x$?

$\endgroup$
3
$\begingroup$

You have:

$\dfrac{1}{2}(1 + e^{-3.6 + 1.8x}) = e^{-3.6 + 1.8x}$, so

$e^{-3.6 + 1.8x} = 1$, and taking logs of both sides, we get

$$-3.6 + 1.8 x = 0$$

I think you can manage the rest.

$\endgroup$
1
  • $\begingroup$ Well done, Amzoti! +1 $\endgroup$
    – amWhy
    Oct 19, 2013 at 1:23
0
$\begingroup$

Initially define $y=\exp(1.8x)$ Then your first equation becomes $0.5=\frac {\exp(-3.6)y}{1+\exp(-3.6)y}$ Solve for $y$, then note that $x = \frac 1{1.8}\log y$

$\endgroup$
0
$\begingroup$

Suppose that $y = \text{exp}(-3.6+1.8x)$. Then your original equation reduces to:

$$0.5 = \frac{y}{1+y}$$

Thus, we have:

$$0.5 (1+y) = y$$

which when simplified yields:

$$y=1$$.

Therefore, we have to solve for:

$$\text{exp}(-3.6+1.8x)=1$$

Now, we know that $e^0=1$. You should be able to find $x$ now.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.